Numerical ecology - Legendre, Pierre, 1946-; Legendre, Louis; Legendre, Louis; Legendre, Pierre, 1946- (Amsterdam ; Boston : Elsevier, 2012)
The book describes and discusses the numerical methods which are successfully being used for analysing ecological data, using a clear and comprehensive approach. These methods are derived from the fields of mathematical physics, parametric and nonparametric statistics, information theory, numerical taxonomy, archaeology, psychometry, sociometry, econometry and others. An updated, 3rd English edition of the most widely cited book on quantitative analysis of multivariate ecological data. Relates ecological questions to methods of statistical analysis, with a clear description of complex numerical methods. All methods are illustrated by examples from the ecological literature so that ecologists clearly see how to use the methods and approaches in their own research. All calculations are available in R language functions.
Complex ecological data sets -- Matrix algebra : a summary -- Dimensional analysis in ecology -- Multidimensional quantitative data -- Multidimensional semiquantitative data -- Multidimensional qualitative data -- Ecological resemblance -- Cluster analysis -- Ordination in reduced space -- Interpretation of ecological structures -- Canonical analysis -- Ecological data series -- Spatial analysis -- Multiscale analysis : spatial eigenfunctions.
Includes bibliographical references and index.
Keywords: Ecology -- Mathematics; Environmental sciences -- Mathematics; SCIENCE -- Life Sciences -- Ecology; Ecology -- Mathematics; Environmental sciences -- Mathematics